Next-Generation Sequencing Reveals Pathway Activations and New Routes to Targeted Therapies in Cutaneous Metastatic Melanoma. (January 2017) - Carlson, J. Andrew; Caldeira Xavier, Jose Candido; Tarasen, Ashley; Sheehan, Christine E.; Otto, Geoff; Miller, Vincent A.; Stephens, Philip J.; Elvin, Julia A.; Vergilio, Jo-Anne; Suh, James; Gay, Laurie M.; Ross, Jeffrey S.
Abstract : Background: Comprehensive genomic profiling of clinical samples by next-generation sequencing (NGS) can identify one or more therapy targets for the treatment of metastatic melanoma (MM) with a single diagnostic test. Methods: NGS was performed on hybridization-captured, adaptor ligation–based libraries using DNA extracted from 4 formalin-fixed paraffin-embedded sections cut at 10 microns from 30 MM cases. The exons of 182 cancer-related genes were fully sequenced using the Illumina HiSeq 2000 at an average sequencing depth of 1098X and evaluated for genomic alterations (GAs) including point mutations, insertions, deletions, copy number alterations, and select gene fusions/rearrangements. Clinically relevant GAs (CRGAs) were defined as those identifying commercially available targeted therapeutics or therapies in registered clinical trials. Results: The 30 American Joint Committee on Cancer Stage IV MM included 17 (57%) male and 13 (43%) female patients with a mean age of 59.5 years (range 41–83 years). All MM samples had at least 1 GA, and an average of 2.7 GA/sample (range 1–7) was identified. The mean number of GA did not differ based on age or sex; however, on average, significantly more GAs were identified in amelanotic and poorly differentiated MM. GAs were most commonly identified in BRAF (12 cases, 40%), CDKN2A (6 cases, 20%), NF1 (8 cases, 26.7%), and NRAS (6 cases, 20%). CRGAs were identified in all patients, and represented 77% of the GA (64/83) detected. The median and mean CRGAs per tumor were 2 and 2.1, respectively (range 1–7). Conclusion: Comprehensive genomic profiling of MM, using a single diagnostic test, uncovers an unexpectedly high number of CRGA that would not be identified by standard of care testing. Moreover, NGS has the potential to influence therapy selection and can direct patients to enter relevant clinical trials evaluating promising targeted therapies. Abstract : Supplemental Digital Content is Available in the Text.